Innovation in development cooperation: emerging trajectories and implications for inclusive sustainable development in the 21st century - Silva, Ana Luísa (Innovation & Development, 2021)
In the past twenty years, innovation has slowly, but steadily, become an important presence in development cooperation discourse and practice. The ambitious UN 2030 Sustainable Development Agenda has accelerated this trend, providing a strong framework for the main argument in favour of an innovation agenda for international development: without new ideas and innovative solutions, solving the current global development challenges will not be possible. Although this innovation-push is in line with a wider predominant view of innovation as an inherently positive force of progress, that alone does not explain when, how, and why innovation becomes a key topic in the field. This paper seeks to fill this gap in the literature, providing an initial overview of innovation in development cooperation in the post-2000s. It argues, firstly, that innovation has always been part of international development policy and practice. Secondly, it links the recent strengthening of the innovation discourse to three trends in the systemic transformation of the field: the triumph of metrics-based agendas, the ICTs and digitalization revolutions, and the role of private sector actors. It concludes by critically assessing the implications of this narrative in changing the politics of innovation towards more inclusive sustainable development policies and practices.
Number: 1
Keywords: Coopération; Invention; Réservé UdeM